Evaluating the effects of a yoga-based program integrated with third-wave cognitive behavioral therapy components on self-regulation in children on the autism spectrum: A pilot randomized controlled trial. (May 2021) - Tanksale, Radhika; Sofronoff, Kate; Sheffield, Jeanie; Gilmour, John
Research using mind–body practices in autism is limited but suggests a trend for ruminative reduction and improved behavioral–emotional outcomes. Following random assignment ( N  = 67), effects of a weekly six-session pilot yoga-based group program combined with third-wave cognitive behavioral therapy elements on self-regulation for children on the autism spectrum (aged 8–12 years) was assessed. The primary outcome was executive functions. Secondary outcomes were sleep, anxiety, and emotion awareness. After attrition, assessment results from participants in the intervention ( n  = 31) and the waitlist conditions ( n  = 30) completed at baseline, post-intervention, and 6-week follow-up were evaluated. For the intervention group, the between-group mean score differences suggest a decrease in parent-reported global executive difficulties from baseline to post-intervention (−2.61; 95% confidence interval −5.13 to −0.09, p   =  0.047, d  = −0.39) and baseline to follow-up (−4.17; 95% confidence interval −6.72 to −1.62, p  = 0.017, d  = −0.59) with small-to-medium effect sizes. Small-to-medium effects were found for a few parent-reported children's sleep issues, child-reported aspects of emotion awareness, and performance anxiety. Non-significant findings are discussed in this article. Preliminary findings suggest mixed results and should be interpreted cautiously. The yoga-informed program may complement existing treatments and will benefit from ongoing evaluation. Lay abstract: Children on the autism spectrum may experience difficulties with the regulation of attention, thoughts, emotions, and behavior, understanding, and expressing their emotions appropriately, as well as anxiety, and sleep. In autism research, contemplative practices that work through both body and mind have shown tentatively promising results. However, there are limited studies on this topic, and the use of yoga to facilitate executive control has not been researched yet. The Incredible Explorers (6-week program), a yoga-informed intervention program for children (8–12 years), was developed to understand whether, for children on the autism spectrum, the training could improve the ability to self-regulate, reduce anxiety and sleep problems, and increase awareness of emotions. In our sample, 61 children with one of their parents completed the program. Half of the group received the intervention, and the other half had to wait until the yoga group completed their trial. The participants were asked to give their feedback immediately after program completion and at 6-week follow-up. Compared to the group that was waiting to receive the intervention, parents in the yoga group reported significant gains for their children in regulating their overall executive control immediately after the session and again at follow-up. The parents reported a reduction in some of the sleep problems post-treatment. Children indicated an improved ability to communicate their feelings and willingness to analyze their emotions post-intervention. However, the study had several shortcomings and given that this was the first trial of the program, the results need to be interpreted with caution. Further research is recommended.